Subject Files Related to the USSR and the Russian Federation - Monitoring Unit
The series contains press clippings from central and republic press, materials from various news agency reports, copies of articles from scientific magazines, RFE/RL research papers. The series reflects political life and economic, media, military, social and cultural issues in the USSR and later the Russian Federation. Of particular interest might be materials related to the political life of the USSR in the transitional period of “perestroika". Accruals not expected